Targeted Protein Degradation: An Important Tool for Drug Discovery for “Undruggable” Tumor Transcription Factors - Mengyuan Dai PhD; Sridhar Radhakrishnan PhD; Rui Li PhD; Ruirong Tan PhD; Kuo Yan PhD; Gang Fan PhD; Miao Liu PhD (Technology in Cancer Research & Treatment, 2022)
Conventional small-molecule drugs (SMDs) are compounds characterized by low molecular weight, high cell permeability, and high selectivity. In clinical translation, SMDs are regarded as good candidates for oral drug formulation. SMD inhibitors play an important role in cancer treatment; however, resistance and low effectiveness have been major bottlenecks in clinical application. Generally, only 20% of cell proteins can potentially be targeted and have been developed as SMDs; thus, some types of tumor targets are considered “undruggable.” Among these are transcription factors (TFs), an important class of proteins that regulate the occurrence, formation, and development of tumors. It is difficult for SMDs and macromolecular drugs to identify bioactive sites in TFs and hence for use as pharmacological inhibitors in targeting TF proteins. For this reason, technologies that enable targeted protein degradation, such as proteolysis-targeting chimera or molecular glues, could serve as a potential tool to solve these conundrums.